Benefits of the group interaction among the HIV-Aids beares - Souza, Nilzemar R.; Vietta, Edna Paciência (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: The study aims the utilization of group approach in nursing like therapeutics alternative in health-place attending of infected peoplewith HIV virus. Objective:to analyze the group process like therapeutics resource and the help in clinical-health-place treatment, to put face to faceinfected people with HIV virus in different stages of illness; to give conditions to exchange of experiences and fall of anguishes, to identify throughstatements of infected people with HIV virus and staff involved in group activity, the advantages and disadvantages in this kind of approach, for theimprovement of life quality of infected people with HIV virus. Methods: from the qualified approach, used the work in group to approach 13 users ofHealth-place school – Nursing College in Passos. The employees of Health-place School represented by 04 nurses, 01 psychologist, 01 dentist, 01academic-nursing assistant, 06 nursing academic and 01 employee of general service sector were part of assessment of the study (interview).Results:the results show that, before this study, the modality of the group facilitates changes on behavior of the subjects considered beneficial for their accep-tation and support on treatment, favor some bigger and better acquaintance between patients and group and that negative feelings happened by the ill-ness, are relieved by emotional support offered by the group. Conclusion:it concluded, with the work, that the group activities must be used by nur-ses like therapeutics resource in treatment of infected people with HIV virus, allowing some valuable space to change the experiences and compre-hension of psychosocial aspects of human being.